FKK’s lecturer biography / Norain Isa - Isa, Norain (Faculty of Chemical Engineering, 2020)
What were your favorite and least favorite chemical engineering classes? Favourite: Heat Transfer Least favourite: Separation process Other than chemical engineering, what field that you are interested to study? Foods and music What was the best memory of your time at UiTM? My favourite memory at UiTM when / first met my husband at Level 9 during Misi Akademik meeting. Where you will be in 10 years from now? Successful lecturer with a balance between teaching and research.